AN INCREASING VALUE OF HYBRID CAPACITORS (GRAPHENE) BASED ON COLLECTOR CROSS-CROSS-CROSS-SIDE - Regen situmorang; Solly Aryza2; Adi Sastra P Tarigan (Sean Institute, 2022)
This study describes the effect of the collector cross-sectional area on the capacitance value of the four graphene super capacitors using a digital multimeter. In the first experiment, the graphene square super capacitor with a cross-sectional area of 25 cm2 resulted in a capacitance of 0.842 F. Especially the super capacitor, which is called a double layer electric capacitor (EDLC) or ultra capacitors, meet the standards for high power applications. The use of supercapacitors is very rare because of the high cost of manufacture. The graphene super capacitor that has the best capacitance is Square. The graphene super capacitor in this study was designed in several stages. Synthesis of graphene as electrode was obtained by mixing H2SO4, H3PO4, KMnO4, Graphite Powder, dried for 12 hours at 110ºC